Cikandang river discharge as a micro-hydropower plant. Issue 2 (March 2021) - Permana, S; Muin, W M F; Johari, G J; Susetyaningsih, A; Nanang, N
Abstract: Garut Regency is flanked by three mountains, namely Papandayan, Guntur, Cikuray. Some are coastal areas in the south of the Garut Regency. Cikandang River has the potential to meet the needs of micro-hydropower plants. The utilization of the Cikandang river is used as a micro-hydropower plant with a power of 1 MW to 10 MW. The locations of the Cikandang 1 and Cikandang 2 micro-hydropower plants nearby use the same potential discharge from the Cikandangriver. In practice, the use of this river has a difference between PLTM Cikandang 1 of 6 MegaWatts and Cikandang 2 of 3 MW. The method is based on a pre-planned design layout. The calculated discharge is the mainstay discharge or the availability discharge calculated based on the FJ Mock method with a probability of 85% with ten years of rain data. Available discharge on the Cikandang river is 12.88 m3/sec, and the head is 32.7 m with head losses 0.86 m, and system efficiency is 0.69. The output power of the Cikandang 2 micro-hydropower plant is 2.88 MW. The difference between the Cikandang 1 and 2 micro-hydropower plants lies in the height of the head.